Role Of Endoscopy To Reduce Extreme Hyperbilirubinemia In Lemmel Syndrome : A Case Report - Rini Suswita (Faculty of Medicine, Universitas Andalas, 2023)
Duodenal diverticulum is a false diverticulum which is generally asymptomatic, frequently founded incidentally at endoscopy and 22% at autopsy. One to five percent of duodenal diverticulum have complications such as bilio-pancreatic complications. Lemmel syndrome is a complication of bilio-pancreatic characterized by jaundice, increased levels of bilirubin, liver and pancreatic enzymes. Reported a male patient, 72 years old, he complained abdominal pain in the right upper quadrant, yellow eyes and body, and dark tea-colored urine. Abdominal pain with Visual Analog Scale (VAS) value between 6 to 7. Blood test resulted prolonged APTT 37